Assessing the identity of digital technology in education in the age of digital communication - Tin Tin Ting; Kuok Tiung Lee; Siew Mooi Lim; Che Ching Lai; Marja Azlima Omar; James Alin; Aisah Meri (Bastas Publications, 2023)
Digital technology has become a part of undergraduate daily life as digital assistant in the age of digital communication (social media and smartphones), purchasing necessities (online shopping), releasing stress (online game) and education resources supply (social media) during or after COVID-19 pandemics especially those involved in online education. However, excessive participation in these technologies raises concerns among the society. The most visible impact will be academic performance, physical and mental health. This research aims to analyze the addiction level and impacts of digital culture in undergraduates who involved in digital education, using empirical study. 320 scholars from a private university are invited to participate in the study. Pearson correlation and descriptive analysis are performed using SPSS in data analysis. The result shows that 62.05% of the respondents fall under a moderate level of addictive digital. Social media addiction, smartphone addiction, online game addiction, and online shopping addiction do not significantly affect undergraduate academic performance, but they have a significant impact on physical and mental health. This research brings new perceptions of different digital technologies to undergraduates in a comprehensive view in terms of digital technology empowerment or endangerment in education in this age of digital communication. This is useful as guidance to policy makers in the future design of online education.